Feasibility study evaluating a magnetic marker in an ex-vivo porcine model - Peek, M; Zada, A; Ahmed, M; Baker, R; Sekino, M; Kusakabe, M; Douek, M (Elsevier, 2018)
The magnetic technique using a magnetic tracer and handheld magnetometer was successfully evaluated in breast surgery. Residual tracer at the injection site can cause susceptibility artefacts on breast magnetic resonance imaging (MRI), therefore for lesion localization a solid marker would be preferable. Four magnetic markers were developed for localization to evaluate its clinical applicability. Methods: Comparison was made of the maximum magnetic counts and artefact-volume on MRI. Results: All markers were successfully detected, the spring marker showed the highest mean magnetic counts (627.8 ± 400.2, mean ± SD) with unequal variances (p <.001) and the butterfly marker showed the smallest mean artefact-volume (11.1 ± 2.3 cm3) with a significant difference between markers (p =.049). Conclusion: Localization using a magnetic marker is feasible and further evaluation is required within a clinical trial.